Entrepreneurial orientation and firm performance of Malaysian SMEs: a systematic review and the uncharted parts - Liew, Mei Xuan; Jamaluddin, Askiah; Zainalaludin, Zumilah; Md. Yusoff, Irwan Syah (SAGE Publications Inc., 2024)
Under NEP2030, aimed at transforming Malaysia into an entrepreneurial nation, this study identifies common themes in research on entrepreneurial orientation(EO)–firm performance (FP) linkages within Malaysian small and medium-sized enterprises (SMEs). It also explores how these themes interact with other variables, highlighting research gaps and suggesting future research avenues. A multi-step systematic review of the empirical literature on EO–FP linkages within Malaysian SMEs was conducted, adopting 19 papers published between 2001 and 2021 from an initial 27 identified through Scopus. The results show that research on EO–FP linkages in Malaysian SMEs is growing by leaps and bounds from 2016 onwards, and even gradually includes moderators and mediators. From here, studies have established that the unidimensional concept of EO dominates; however, whether services are more likely to form positive EO–FP linkages than manufacturing has not been explored; FP is measured primarily by financial indicators. Meanwhile, subjective measures were the only option in 19 studies. This study shows why, when, and how the EO–FP linkages work. These are context-specific (i.e., Malaysian SMEs), highlighting the integration of many pieces to generate new ideas. These ideas provide a possible agenda for future research on EO–FP linkages, particularly suitable for SMEs facing a sustainable economic framework.